2015
DOI: 10.1186/s12879-015-1301-5
|View full text |Cite
|
Sign up to set email alerts
|

HIV treatment and care among Italian inmates: a one-month point survey

Abstract: BackgroundHIV infection, with an estimated prevalence be between 2 and 50 times those of the general adult population is a major health challenge for prison authorities worldwide. Since no nationwide surveillance system is present in Italy, data on HIV prevalence and treatment in prisons are limited to only a few and small observational studies. We aimed to estimate HIV prevalence and obtain an overview on diagnostic and therapeutic activities concerning HIV infection in the Italian penitentiary system.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 56 publications
2
19
0
4
Order By: Relevance
“…In a South African prison, losses to follow up among 148 prisoners were high (22%) both during incarceration and after release but in the 70 patients who remained in care, 92% had an undetectable VL [16]. Our virological results and those of the South African study compare favourably with reports from prisons in affluent settings where rates of undetectable VL were between 50 and 74% [8][9][10][11] as well as with recent routinely collected VL data from the whole population on ART in Malawi, showing that 11% of VL results were >1,000 copies/ml [17].…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…In a South African prison, losses to follow up among 148 prisoners were high (22%) both during incarceration and after release but in the 70 patients who remained in care, 92% had an undetectable VL [16]. Our virological results and those of the South African study compare favourably with reports from prisons in affluent settings where rates of undetectable VL were between 50 and 74% [8][9][10][11] as well as with recent routinely collected VL data from the whole population on ART in Malawi, showing that 11% of VL results were >1,000 copies/ml [17].…”
Section: Resultssupporting
confidence: 64%
“…In Connecticut USA, 70% of 882 prisoners on ART between 2005 and 2012 had undetectable VL before release from prison [9] and achieving full viral suppression was associated with female gender and a lower psychiatric illness score. In 275 Italian prisoners on ART, optimal virological results were observed in 74% in a report from 2013 [10] and in an audit of HIV care in British prisons 68% of 74 prisoners on ART had full HIV suppression [11].…”
Section: Introductionmentioning
confidence: 99%
“…12,19 In relation to testing and counseling, a study conducted in Italy in 2013 found that all PUs studied offered HIV testing. 13 Another study conducted in Malaysia found that 66.9% of participants were diagnosed with HIV in a previous incarceration, 56.5% in the current incarceration and 10.5% by compulsory testing during incarceration. 14 It is noteworthy that this last study includes elements of the cascade of care before incarceration and during prison, considering the diagnosis, retention of care (offer of TCD4+) and ART prescription, however, disease prevention, therapeutic adherence and viral suppression were not explored.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding their approach, seven were quantitative (three descriptive, two cross sectional and two descriptive / cross sectional) and two were qualitative (Table 1). The care provided to people with HIV/AIDS in prison was addressed by the articles regarding the following themes: HIV prevention,12,19 HIV testing and diagnosis,13-16 HIV treatment, [13][14][15][16] Articulation with health services in addressing HIV. 12,15,18,20 In the HIV prevention theme, it was found that the development of such action within the PU can be an alternative to decrease the number of new cases of detainees infected with the virus, 19 however there are prisons that represent a high-risk environment for the HIV transmission.…”
Section: Resultsmentioning
confidence: 99%
“…Para que a prevenção combinada seja eficaz, pressupõe-se adequação na realidade local da população em que as intervenções serão direcionadas, levando em consideração os contextos, práticas e processos identitários dos sujeitos (BRASIL, 2018b). Por exemplo, os testes rápidos no sistema prisional mostram-se eficazes no diagnóstico oportuno de PPL, uma vez que parte deles realiza o teste durante a detenção; contudo, fazer parte da ação não significa que o indivíduo aceitará o diagnóstico ou iniciará o tratamento, reforçando a necessidade de ações individuais singulares e sigilosas(MONARCA et al, 2015;BICK et al, 2016;SPAULDING et al, 2013;SIMONSEN et al, 2015). Além disso, mesmo que o teste rápido para HIV seja uma alternativa na identificação de pessoas com a infeção pelo vírus nas UP, barreiras envolvendo a logística de disponibilização de insumos podem estar presentes para o desempenho desta ação no âmbito institucional(SIMONSEN et al, 2015).Vale ressaltar ainda a estratégia designada "TasP" (Treatment as Prevention), ou seja, tratamento como prevenção, a qual representa uma das inovações propostas junto à PreP e à PEP sexual.…”
unclassified